The Alcohol Environment Protocol: A new tool for alcohol policy. (4th January 2018) - Casswell, Sally; Morojele, Neo; Williams, Petal Petersen; Chaiyasong, Surasak; Gordon, Ross; Gray‐Phillip, Gaile; Viet Cuong, Pham; MacKintosh, Anne‐Marie; Halliday, Sharon; Railton, Renee; Randerson, Steve; Parry, Charles D. H.
Abstract: Introduction and Aim: To report data on the implementation of alcohol policies regarding availability and marketing, and drink driving, along with ratings of enforcement from two small high‐income to three high‐middle income countries, and one low‐middle income country. Method: This study uses the Alcohol Environment Protocol, an International Alcohol Control study research tool, which documents the alcohol policy environment by standardised collection of data from administrative sources, observational studies and interviews with key informants to allow for cross‐country comparison and change over time. Results: All countries showed adoption to varying extents of key effective policy approaches outlined in the World Health Organization Global Strategy to Reduce the Harmful Use of Alcohol (2010). High‐income countries were more likely to allocate resources to enforcement. However, where enforcement and implementation were high, policy on availability was fairly liberal. Key Informants judged alcohol to be very available in both high‐ and middle‐income countries, reflecting liberal policy in the former and less implementation and enforcement and informal (unlicensed) sale of alcohol in the latter. Marketing was largely unrestricted in all countries and while drink‐driving legislation was in place, it was less well enforced in middle‐income countries. Conclusion: In countries with fewer resources, alcohol policies are less effective because of lack of implementation and enforcement and, in the case of marketing, lack of regulation. This has implications for the increase in consumption taking place as a result of the expanding distribution and marketing of commercial alcohol and consequent increases in alcohol‐related harm.